PENGARUH ASIMETRI INFORMASI, LEVERAGE, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL PADA MANAJEMEN LABA - Utari, Ni Putu Linda Ayu; Sari, Maria M. Ratna (E-Jurnal Akuntansi, 2016)
The purpose of this study was to obtain empirical evidence of the influence of asymmetry of information, leverage, managerial ownership and institutional ownership on earnings management. This study was performed on companies listed on the Stock Exchange 2009-2013 period. The sample is determined by using purposive sampling method. The samples selected were 185 companies observations. Data analysis technique used is multiple linear regression analysis. But before doing multiple linear regression analysis, first performed classical assumption. Based on the analysis that has been done, this study proves that the asymmetry of information and leverage positive effect on earnings management, managerial ownership and institutional kepenilikan negative effect on earnings management.
Keywords: Information Asymmetry, Leverage, Managerial Ownership, Institutional Ownership, Earnings Management